2022
DOI: 10.2147/jir.s352706
|View full text |Cite
|
Sign up to set email alerts
|

Gegen Qinlian Decoction Alleviates Experimental Colitis and Concurrent Lung Inflammation by Inhibiting the Recruitment of Inflammatory Myeloid Cells and Restoring Microbial Balance

Abstract: Objective Ulcerative colitis (UC) as one of the intractable diseases in gastroenterology seriously threatens human health. Respiratory pathology is a representative extraintestinal manifestation of UC affecting the quality of life of patients. Gegen Qinlian Decoction (GQD) is a classical traditional Chinese medicine prescription for UC or acute lung injury. This study was aimed to reveal the therapeutic effect of GQD on UC and its pulmonary complications and uncover its molecular mechanism mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…34 In our previous study, we found inflammatory monocyte and macrophage infiltration in colitis-induced lung injury, in agreement with our present findings. 9 Moreover, we further found that the high doses of probiotic BL-99 effectively inhibited the infiltration of inflammatory cells in the lungs of colitis mice. Immediately, we proceeded towards exploring the regulation between the gut microbes and metabolites on inflammatory cells.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…34 In our previous study, we found inflammatory monocyte and macrophage infiltration in colitis-induced lung injury, in agreement with our present findings. 9 Moreover, we further found that the high doses of probiotic BL-99 effectively inhibited the infiltration of inflammatory cells in the lungs of colitis mice. Immediately, we proceeded towards exploring the regulation between the gut microbes and metabolites on inflammatory cells.…”
Section: Discussionmentioning
confidence: 76%
“…Inflammatory (Inflam) monocytes were identified as CD45 + CD11b + CD11c − Ly6C hi , and macrophages were identified as CD45 + CD11b + F4/80 + cells. 9,24 Single-cell suspensions were kept at 4 °C, and nonspecific binding was blocked by an anti-Fc receptor-blocking antibody (anti-CD16/32) before the cell surface was stained with fluorescently conjugated antibodies. The cells were then stained with PB anti-mouse CD45, PE-Cy5 anti-mouse CD11b, FITC anti-mouse CD11c, APC-Cy7 anti-mouse Ly6C, and F4/80 anti-mouse AF700.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
See 3 more Smart Citations